The Correlation Between Arabic Learning Content on the Instagram Account @arabiyahtalks and the Learning Interest of Grade X Students : English - Intan, Qori; Desky Halim Sudjani; Agus Mulyana (Tatsqifiy: Jurnal Pendidikan Bahasa Arab, 2026)
This research is motivated by challenges in Arabic language learning within formal schools, where students tend to experience boredom due to conventional instructional patterns, while the potential of social media as an educational tool has not been optimally utilized. This study aims to examine the correlation between the utilization of learning content on the @arabiyahtalks Instagram account and the learning interest of tenth-grade students at MAN 1 Bogor. Using a quantitative correlational design, data were collected through Likert-scale questionnaires distributed to 34 respondents using simple random sampling. Data analysis was performed using Pearson Product-Moment correlation and the coefficient of determination via SPSS 26. The results indicate a very strong positive correlation between the two variables, with a correlation coefficient (r) of 0.917. Furthermore, the coefficient of determination shows that @arabiyahtalks content contributes 84.1% to students’ learning interest, while the remaining 15.9% is influenced by other factors. These findings prove that the synchronization between independent digital media based on micro-learning and formal environments can serve as an effective catalyst in reconstructing students’ interest in learning Arabic in the digital disruption era.